PENERAPAN METODE PEMBELAJARAN LEARNING TOGETHER (LT) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) KELAS X IPA DI MA MIFTAHUL JANNAH PERANAP KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Gusrita Yeni; Sopiatun Nahwiyah; Alhairi Alhairi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
This research is motivated by the low learning motivation of class X science students in the subject of Islamic Cultural History at MA Miftahul Jannah Peranap. Role of Indragiri Hulu Regency with data collection teacniques through observation, interviews and dokumentation. The method used this research is the Learning Together (LT) method, which is a learning method in which students are placed in small groups. Each group was asked to produce one group assignment. And the results showed that learning using the Learning Together learning method could increase students’ learning motivation, this can be seen and the results of the Pre-cycle students’ learning motivation only reached 24,99% in Cycle I increased to 44,99%, and in Cycle II it rose to 71,66%, it can be concluded that the application of the Learning Together learning method implemented in SKI Learning can increase the learning motivation of class X science students at MA Miftahul Jannah Peranap, District Peranap, Indragiri Hulu Regency.